Embodied collaborative writing in graduate dance education - Markula, Pirkko; Frantsi, Janita (Frontiers in Sports and Active Living, 2024)
This paper explores how embodied writing can inform teaching, learning, and research presentation in graduate-level dance education in a kinesiology faculty. The focus is on a graduate dance course “The Dancing Body in Motion”, which combines the anatomical analysis of the physical body, social theory, and lived dance experiences to promote more embodied and holistic teaching and learning. The authors, an instructor and a student of the course, share their experiences and reflections on the course through an embodied presentation of a dialogue that combines the instructor’s lecture notes, the student’s learning journal entries, and their reflections both separately and in conversation with each other. Their reflections offer insights into how the body and mind, material and social body, and practice and theory can all be brought together using embodied writing practices, such as a learning journal and performance ethnography, in a dance performance.